Deformation characteristics in 3D free-bending forming of complex spiral tubes. Issue 1 (November 2020) - Abd El-Aty, A; Wei, W; Guo, X; Wang, H; Tao, J; Chen, H; Qin, Y
Abstract: Free-bending is a novel bending technology suitable for tube and profile bending. It can achieve accurate bending of tubes or profiles with different bending radii without die. In current study, a new theoretical analysis of a spiral tube formed by 3D free-bending is proposed to reveal the relationship between the spiral tube and the parameters of free-bending forming technology. The results obtained from the proposed theoretical analysis were compared with those achieved from FE modelling and experimentation. The maximum error of forming was less than 7%, which verified the accuracy and the reliability of the proposed theoretical model. The forming limits of the spiral tubes based on 3D free-bending were explored. It was noticed that the spiral diameter was mainly influenced by the eccentricity and the distance between the center of the bending die and the front end of the guide mechanism in the Z–direction (distance A). Furthermore, the spiral diameter is inversely proportional to the eccentricity, and directly proportional to the distance A. In addition, the screw pitch is mainly influenced, and directly proportional to the spiral diameter and the single spiral circle swing angle of the spherical bearing.